Combined effects of irradiation and storage time on the nutritional and chemical parameters of dried Agaricus bisporus Portobello mushroom flour - Cardoso, Rossana V.C. (2018)
Abstract: Portobello variety of Agaricus bisporus mushrooms, appreciated for its taste, makes it desirable to be eaten fresh and also as flour in soups and gravies. Gamma and electron-beam radiation at four doses (1, 2, 5, and 10 kGy) were used to analyze its preservation effect on Portobello mushroom flour. A proximate analysis, as well as the impact on fatty acids, tocopherols, soluble sugars, organic acids, and ergosterol profiles, were performed every 3 months, during a storage period of 1 year. Gamma rays preserved mannitol (most abundant soluble sugar) over the 12 months, while electron beam radiation preserved organic acids. No significant changes were sought for any radiation type, and the slight changes extracted from the estimated marginal means reveal a tendency for irradiation as having preserving effects of nutrients and other important molecules. Thus, both irradiation types, up to 10 kGy are suitable for preservation of A. bisporus Portobello flour.